CD8+XCR1neg Dendritic Cells Express High Levels of Toll-Like Receptor 5 and a Unique Complement of Endocytic Receptors - Wylie, Ben; Read, James; Buzzai, Anthony C.; Wagner, Teagan; Troy, Niamh; Syn, Genevieve; Stone, Shane R.; Foley, Bree; Bosco, Anthony; Cruickshank, Mark N.; Waithman, Jason (Frontiers in Immunology, 2019)
Conventional dendritic cells (cDC) resident in the lymphoid organs of mice have been classically divided into CD8+ and CD8neg subsets. It is well established that CD8+ dendritic cells (DCs) and their migratory counterparts in the periphery comprise the cross-presenting cDC1 subset. In contrast, CD8neg DCs are grouped together in the heterogeneous cDC2 subset. CD8neg DCs are relatively poor cross-presenters and drive more prominent CD4+ T cell responses against exogenous antigens. The discovery of the X-C motif chemokine receptor 1 (XCR1) as a specific marker of cross-presenting DCs, has led to the identification of a divergent subset of CD8+ DCs that lacks the ability to cross-present. Here, we report that these poorly characterised CD8+XCR1neg DCs have a gene expression profile that is consistent with both plasmacytoid DCs (pDCs) and cDC2. Our data demonstrate that CD8+XCR1neg DCs possess a unique pattern of endocytic receptors and a restricted toll-like receptor (TLR) profile that is particularly enriched for TLR5, giving them a unique position within the DC immunosurveillance network.